Comparative analysis of the legal bibliography class on selected law schools in the Metro Manila Area - Buenaventura, Joshua S.; Santos, Antonio M. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2002)
The study aimed to pinpoint the characteristics that affect the competence and performance of law students in the way they do legal research. The study surveyed six (6) law schools in the Metro Manila Area, namely, the Ateneo De Manila University, Ateneo Law School; Manuel L. Quezon University, School of Law; San Sebastian College-Recoletos, Institute of Law, University of the East, College of Law, University of the Philippines, College of Law; and the University of Santo Tomas, Faculty of Civil Law. The total numbers of respondents were three hundred twenty three (323)The study deduced that there are several factors that affect the level of competence and performance of law students. First among these factors is the collection of the library. The collection of the library either supplements or limits the capability of the law student to do legal research. Second, is the incorporation of technology such as computers, Internet access, online catalogs, CD-ROMs, and databases. Having an automated law library affects the law student by keeping him/her attuned to technologies that can be used to make research more accessible and less time consuming. Third is the teacher, professor, or instructor who directly affects law students since they are the primary source on the knowledge on how to do legal research the background of the teacher, professor or instructor can play an important role in establishing good research skills, at the same time an understanding of the law books. Lastly, the curriculum which plays a key role in the law student's competence and performance. By having a good curriculum that ensures the incorporation of the latest technological advancement and in debt legal principles, the institutions would be able to train and prepare law students to succeed in their future endeavors as practitioners of the law.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Law schools -- Philippines -- Manila Metropolitan Area; Legal research -- Philippines